A specific olfactory bulb interneuron subtype Tpbg/5T4 generated at embryonic and neonatal stages - Tsuboi, Akio (Frontiers in Neural Circuits, 2024)
Various mammals have shown that sensory stimulation plays a crucial role in regulating the development of diverse structures, such as the olfactory bulb (OB), cerebral cortex, hippocampus, and retina. In the OB, the dendritic development of excitatory projection neurons like mitral/tufted cells is influenced by olfactory experiences. Odor stimulation is also essential for the dendritic development of inhibitory OB interneurons, such as granule and periglomerular cells, which are continuously produced in the ventricular-subventricular zone throughout life.Based on the morphological and molecular features, OB interneurons are classified into several subtypes. The role for each interneuron subtype in the control of olfactory behavior remains poorly understood due to lack of each specific marker. Among the several OB interneuron subtypes, a specific granule cell subtype, which expresses the oncofetal trophoblast glycoprotein (Tpbg or 5T4) gene, has been reported to be required for odor detection and discrimination behavior. This review will primarily focus on elucidating the contribution of different granule cell subtypes, including the Tpbg/5T4 subtype, to olfactory processing and behavior during the embryonic and adult stages.